Research progress of Retention enema with Traditional Chinese Medicine in the treatment of sequelae of pelvic inflammatory disease (中药保留灌肠治疗盆腔炎性疾病后遗症的研究进展) - ZHUANG Qizhen (庄琪珍); WU Suya (吴素雅) (中西医结合护理)
Pelvic inflammatory disease and its sequelae are common and frequently occurring diseases. Retention enema with Traditional Chinese medicine is widely used in the treatment of sequelae of pelvic inflammatory disease, which can effectively improve clinical symptoms, promote disease recovery and improve patients’ quality of life. This paper reviewed the study about chronic pelvic inflammation in Traditional Chinese Medicine and related treatment and nursing of sequelae of pelvic inflammatory disease, in order to improve the efficacy of clinical treatment and quality of nursing. (盆腔炎性疾病后遗症是妇科常见病、多发病之一, 具有反复发作、缠绵难愈的特点。中药保留灌肠治疗盆腔炎性后遗症临床应用广泛, 能有效改善临床症状, 促进疾病恢复, 改善生活质量。本研究就中医对慢性盆腔炎及其后遗症的认知以及中药保留灌肠对盆腔炎性疾病后遗症的治疗和护理进行综述, 以期为进一步提高盆腔炎性疾病后遗症临床治疗和护理提供参考。)